Effects of royal jelly on sterile skin cut repair - Shirzad Maryam; Yousofi Mahboubeh; Zamanzad Behnam; Sedaghat Akram; Hosseini Masih; Shahinfard Najmeh; Shirzad Hedayatollah (Shahrekord University of Medical Sciences, 2014)
Introduction: Following injury, inflammatory response occurs and the cells below the dermis begin to increase collagen production, then, the epithelial tissue is regenerated. Royal jelly (RJ) has anti-inflammatory activity hence, the aim of this study was to examine the effect of RJ on the induction of sterile skin incision in Balb/C mice.Methods: In an experimental study 60 female Balb/C mice (8 weeks old) were anaesthetized with ether and a longitudinal para vertebral full thickness incision of 10 mm long was made. The animals were divided into six equal groups. Group 1 was considered as negative control. Group 2 (positive control) was treated topically with Nitrofurazon ointment, group 3 with RJ (200 mg/kg) every day, group 4 with RJ (200 mg/kg) every two days, group 5 with RJ (300 mg/kg) every day and group 6 with RJ (300 mg/kg) every two days. The wound length was measured with vernier capilar every two days up to full healing occurred and compared in different groups. Results: There was significant difference between groups 1 or 2 and other groups (p<0.05). RJ promoted wound healing activity significantly in group 3, 5 compared to negative and positive control groups. There was no significant difference between the uses of 200 mg/kg and 300 mg/kg RJ (p>0.05). Conclusion: The results of this study indicate that daily application of RJ possesses betters wound healing effects than Nitrofurazon and every two days usage of RJ.